2016
DOI: 10.1039/c5gc02314a
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-free Pd catalyzed cross-coupling reactions in an aqueous hydrotropic medium

Abstract: A simple, efficient and ligand-free protocol for the Suzuki–Miyaura reaction and base-free Heck–Matsuda reactions under mild reaction conditions has been developed over palladium supported on activated carbon (Pd/C) in an aqueous hydrotropic solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 84 publications
0
33
0
Order By: Relevance
“…ICP analysis showed that after the reaction was completed, almost all the dissolved Pd species could redeposit on the support, so the catalyst had good recyclability. Similarly, Salunkhe and coworkers showed Pd/C to be an efficient catalyst to couple aryl bromides, arenediazonium salts and acid chlorides with phenylboronic acids by an addition of sodium xylene sulfonate (NaXS) under mild conditions (entry 5) . A control experiment conducted in water provided only a 20% yield in 12 hr.…”
Section: Activated Carbonmentioning
confidence: 98%
See 1 more Smart Citation
“…ICP analysis showed that after the reaction was completed, almost all the dissolved Pd species could redeposit on the support, so the catalyst had good recyclability. Similarly, Salunkhe and coworkers showed Pd/C to be an efficient catalyst to couple aryl bromides, arenediazonium salts and acid chlorides with phenylboronic acids by an addition of sodium xylene sulfonate (NaXS) under mild conditions (entry 5) . A control experiment conducted in water provided only a 20% yield in 12 hr.…”
Section: Activated Carbonmentioning
confidence: 98%
“…successfully achieved high chemo‐ and stereoselectivities in the Heck coupling between aryl iodides and acrylate derivatives by adding cyclodextrin to the isooctane and water multiphase solvent system, and the key parameter was the adsorption of cyclodextrin on the Pd/C solid . In addition, Salunkhe and coworkers developed an efficient base‐free protocol for Heck reactions in an aqueous hydrotropic medium under mild conditions . With the addition of sodium xylene sulfonate (NaXS), the reaction between 4‐nitrodiazonium tetrafluoroborate and methyl acrylate catalyzed by 10% Pd/C produced a styrene derivative with 93% conversion after 1 h of reaction at room temperature.…”
Section: Activated Carbonmentioning
confidence: 99%
“…These reactions provide new roads for design and preparation of drug substances . For example, the cross‐coupling reactions are considered as key steps in production of Losartan®, Zyprexa, Singulair, (+)‐Dynemicin, Morphine and Paclitaxel . The importance of scientific advances associated with cross‐coupling was demonstrated by awarding Richard F. Heck, Ei‐ichi Negishi and Akira Suzuki the Nobel Prize in chemistry in 2010 for the development of palladium‐catalyzed cross coupling …”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, heterogeneous Pd catalytic systems are preferred for industrial applications because of their easy recovery and separation from reaction systems . Consequently, immobilization of Pd catalysts on supports such as polymers, silica, carbon and metal oxides has been extensively investigated in Suzuki–Miyaura reactions. However, some of these heterogeneous Pd catalysts have a lower activity in comparison with their counterpart homogeneous systems …”
Section: Introductionmentioning
confidence: 99%